DRUG ABUSE PREVENTION MODEL FOR ADOLESCENTS THROUGH THE CONCEPT OF ISLAMIC EDUCATION - Bahri, Saiful; Hayati, Nursri (Universitas Islam Negeri Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2024)
Various ways have been done by the National Narcotics Board, Government, Parents, community leaders and other organizations in the prevention of drug abuse against teenagers in the field so that teenagers avoid drug abuse, but the reality in the field is that there are still many teenagers who abuse drugs, seeing these dynamics, in this researcher the researcher conducts an in-depth study of the prevention of drug abuse for adolescents through the concept of Islamic education, with the hope that by finding this abuse prevention model can help in preventing drug abuse for adolescents. in this study researchers used qualitative research studies (library research) with a text analysis approach. Library research is carried out using library references, either in the form of books, journals, messages or the results of previous research information. After collecting the data that the author gets from the source, then the researcher analyzes its contents and determines the themes related to the concept of Islamic Education. Then the results found that the drug abuse prevention model for adolescents through the concept of Islamic Education is the concept of ta'lim, with a prevention pattern, namely, a process of providing knowledge, understanding, understanding, responsibility and instilling trust